Self-Domestication Underground? Testing for Social and Morphological Correlates of Animal Personality in Cooperatively-Breeding Ansell’s Mole-Rats (Fukomys anselli) - Begall, Sabine; Bottermann, Lea; Caspar, Kai Robert (Frontiers in Ecology and Evolution, 2022)
Ansell’s mole-rats (Fukomys anselli) are sexually dimorphic subterranean rodents that live in families consisting of a single breeding pair and their late-dispersing non-breeding offspring. Most individuals exhibit a conspicuous white head patch, which results from integumental depigmentation. Alongside other morphological, physiological, and social characteristics, skin depigmentation in these social rodents mirrors traits that presumably evolved as byproducts from selection against aggression in domestic animals, making them a potential candidate species for a self-domesticated wild mammal. Here we explored whether the expression of the white head patch, sexual dimorphism, and reproductive division of labor are reflected by different animal personalities in Ansell’s mole-rats. We tested locomotory activity and risk-taking as well as aggression and affiliative behaviour in 51 individuals originating from nine captive families in various experimental set-ups. In line with the concept of animal personality, we recovered consistent individual responses over time. While sex had no influence on any tested variable, reproductive status was found to affect risk-taking behaviour but not other personality dimensions. Discriminant function analysis revealed that family members clustered more closely together than expected by chance, suggesting that group affiliation rather than sex or social status determines behavioural profiles in this species. Finally, we failed to recover any consistent correlation between head patch expression and behaviour, which conflicts with predictions of the self-domestication hypothesis. We argue that many domestication-like traits in Ansell’s mole-rat and its congeners evolved in the framework of subterranean adaptation and call for a cautious application of the self-domestication concept to wild mammals.